Fungsi Hukum Sebagai Bagian Dari Penguatan Ekonomi Di Indonesia - Umami, Rizal; jafar, M. Ulfatul Akbar; Zitri, Ilham (Jurnal Ilmiah Mandala Education (JIME), 2022)
Law in its existence in society has a role and influence on economic activities in accordance with the function of the law itself. The law in its function contains instructions for human behavior, tools for resolving conflicts and tools for socioeconomic engineering. Economic development cannot be separated from the development of law, because between economics and law it is two things that affect each other. Law as a provision that is normative has a very important role and function in the economic field. This research will use normative legal research methods. In this normative research uses literature materials as a source of research data (Library Research) methods used to collect data from various literature. This research is descriptive analysis means that this study includes the scope of research that describes, examines, explains appropriately and analyzes the laws and regulations related to this research. This research will produce two analyses, namely related to the relationship between law and economics and legal function in the basis of economic development in Indonesia where the legal task in the field of economics is primarily to be able to always maintain and create safety rules so that the implementation of economic development will not sacrifice the rights and interests of the weak.